Abram os livros, por favor...: representações de ensino aprendizagem de música nos conteúdos do livro didático de Arte do PNLD (2015 a 2017) - Souza, Karla Beatriz Soares de (2018)
This work aims to reflect on the challenges that mark contemporary school music education, especially the importance of the didactic book in the process of teaching musical learning lived in school, with the objective of understanding the representations of music teaching from the present musical contents in Art textbooks, PNLD-Arte (2015-2017). The time cut from 2015 onwards is justified because it is a period in which the curricular component Art has come to becontemplated by the National Program of Didactic Book-PNLD / art. The theoretical references adopted were the studies that comprise music education as a social practice, by Jusamara Souza (1997, 2001, 2004, 2014) and Roger Chartier's conceptions of representation (1990, 1996, 2000, 2011). This documentary-analytical research provided relevant information for reflections on the pedagogical-musical conceptions present in the books adopted as material resources in the basic education schools of every country. Based on these premises, it was possible to identify how the representation of what is musical education or teaching school musical learning is related to the conception of an identity, a domain, the establishment of a collectivity through the materiality of the textbook of Art. The reflections presented may promote public policies for teaching music in school, the production of specific didactic material, and contribute to the training of music teachers.